Rhodium-catalysed enantio- and diastereoselective C(sp2)-C(sp3) cross-coupling reactions - Goetzke, FW (2021)
In this thesis, we describe a series of Rhodium-catalysed enantio- and diastereoselective C(sp2)–C(sp3) cross-coupling reactions and perform brief mechanistic studies in order to understand their underlying mechanisms.